Evaluasi Keberlanjutan Usahatani Sayuran Dalam Sistem Agroforestry Di Daerah Aliran Sungai (DAS) Brantas Hulu, Jawa Timur, Indonesia Dengan Metode Multi Dimensional Scaling (MDS) - Suhartini, Suhartini; Maulana Ishaq, Rizki; Sandi Lasitya, Daffa; Mujaddid, Muhammad Ashri; Nur Jihad, Baroroh; Harun, Adiva A. Y. P.; Bahiyah, Khofifah Nailatul; Yudha Arcelia, Deva (Department of Agricultural Social Economics, Faculty of Agriculture, Brawijaya University, 2024)
Sustainable agricultural system is an agricultural system that is ecologically viable (environmentally friendly), economically viable and socially acceptable and does not conflict with the culture of the local community. The Upper Brantas River Basin (DAS) is one of the most strategic areas in East Java Province, Indoensia, because of its function as an area for providing raw water and producing environmental services. However, as time goes by, population growth in the area continues to increase, this can causing high pressure on land use for settlements, increasingly intensive agriculture, even on land with a slope of more than 30 degrees. One way to overcome this problem is by implementing agroforestry. The aim of this research is to evaluate the sustainability of vegetable farming using an agroforestry system from ecological, economic and socio-cultural dimensions in the Upper Brantas Watershed Area, as well as analyzing sensitive attributes that influence sustainability status. The number of respondents in this research is 60 which consist of farmers who have selected randomly, key informan and stakeholders. The data analysis method used is Multidimensional Scaling (MDS) through the Rap-farm coordination technique. The results of the research show that vegetable farming in the Upper Brantas watershed in the agroforestry system has a sustainability status that is in the 'moderately sustainable' category with an index score in the ecological dimensions of 76.30 (very sustainable), economic of 54.83 (quite sustainable) and social culture of 63.06 (quite sustainable). Sensitive attributes in the ecological dimension are waste recycling and livestock ownership, the economic dimension is land ownership and marketing of agricultural products, and the socio-cultural dimension is the health level of farming households.